Transjugular local thrombolysis with/without TIPS in patients with acute non-cirrhotic, non-malignant portal vein thrombosis. Issue 12 (December 2017) - Klinger, Christoph; Riecken, Bettina; Schmidt, Arthur; De Gottardi, Andrea; Meier, Benjamin; Bosch, Jaime; Caca, Karel
Abstract: Background & aims: Therapeutic anticoagulation is the standard treatment in patients with acute non-cirrhotic portal vein thrombosis (PVT). In critically ill patients, anticoagulation only may not suffice to achive rapid and stable recanalization. This study evaluates efficacy and safety of transjugular interventional therapy in acute non-cirrhotic PVT. Methods: This retrospective study includes 17 consecutive patients with acute noncirrhotic, non-malignant PVT. Main indication for interventional therapy was imminent intestinal infarction (n = 10). Treatment consisted of a combination of transjugular thrombectomy, local fibrinolysis and – depending on thrombus resolution – transjugular intrahepatic portosystemic shunt. Results: Recanalization was successful in 94.1%. One- and two-year secondary PV patency rates were 88.2%. Major complications (n = 3) resolved spontaneously in all but one patient (heparin induced thrombocytopenia type 2 with intestinal infarction). Symptoms improved in all patients. However, segmental bowel resection had to be performed in two (11.8%). During a median follow-up of 28.6 months, no patient experienced portal hypertensive complications. Presence of JAK2 V617F mutation predicted both short-term and long-term technical success. Conclusions: Transjugular recanalization is safe and effective in patients with acute non-cirrhotic, non-malignant PVT. It should be considered especially in patients with imminent bowel infarction and low likelihood of recanalization following therapeutic anticoagulation. Patients with JAK2 mutation ought to be followed meticulously.